Visceral leishmaniasis in a patient with ulcerative colitis: A case report - Janković Goran; Martinović Lena; Dakić Zorica; Mijač Dragana; Štulić Miloš; Krstić Miodrag (Vojnosanitetski Pregled)
Introduction. There is a rise of visceral leishmaniasis in immunocompromised patients due to increased availability of immunomodulatory drugs. In order to point at the occurrence of visceral leishmaniasis in patients with inflammatory bowel disease (IBD), we reported a case of female patient with a travel history to European Mediterranean countries, who was on immunosuppressive treatment due to ulcerative colitis. Case report. A 29-year-old female patient was admitted to hospital due to severe relapse of ulcerative colitis. Corticosteroid therapy was administered in addition to previous longterm azathioprine, with clinical response to the treatment. During the course of the disease she had recurrent high-grade fever with marked hepatosplenomegaly and pancytopenia. The diagnosis of leishmaniasis was established by positive serology tests and microscopic finding of amastigotes in bone marrow smears. The disseminated infection was responsive to treatment with liposomal amphotericin B, but therapy had to be discontinued due to urticarial rush. Subsequent therapy with antimony was administered, but it had to be stopped too due to liver toxicity. No further treatment for leishmaniasis was initiated as the clinical and laboratory data suggested that the patient had responded to the treatment. She was discharged from hospital in IBD remission and without signs of the infection. Conclusion. Visceral leishmaniasis should be considered in IBD patients with fever of unknown origin and relevant travel history in order to achieve favorable disease outcome.